'Strategic coupling' and regional development in a transition economy: what can we learn from Vietnam?. Issue 4 (2nd October 2019) - Wrana, Jöran; Nguyen, Thi Xuan Thu
ABSTRACT: In starting the reform of its socialist-oriented market economy in 1986, the Vietnamese government recognized the crucial role of the private sector in accelerating economic development. However, private domestic firm-driven regional economic development is so far limited due to the absence of a suitably skilled labour force. The coupling of private domestic firms with foreign firms has had a limited impact on productivity, and while multinational German and Japanese enterprises have established cooperative technical vocational and educational training organizations, the spillovers from these initiatives to private domestic firms are limited especially in the Red River Delta area.